math

multiply then simplify by factoring if possible

√3 √6=

  1. 👍 0
  2. 👎 0
  3. 👁 122
  1. sqrt(3)*sqrt(6)=sqret(3*6)=sqrt(18)=sqrt(9*2)

    sqrt(9)=3

    sqrt(9*2)=3*sqrt(2)

    sqrt(3)*sqrt(6)= 3*sqrt(2)

    1. 👍 0
    2. 👎 0

Respond to this Question

First Name

Your Response

Similar Questions

  1. Algebra

    1. solve 3-w/6-w = 3/w-6 2. Find the LCM of (8+9z), (64-81z^2), and (8-9z) 3. Multiply and simplify: 7z^8/10r^2 * 100r^4/49z 4. Add and simplify 2/v + 3/v^2 5. t/5-5t=0

    asked by Anonymous on November 19, 2010
  2. math,algebra

    Use the five properties of exponents to simplify each of the following expressions (y^5)^3(y^3)^2 divided by (y^4)^4 can someone show me how to solve these types of problems (y^5)^3= y^15 multiply the powers (y^3)^2=y^6 multiply

    asked by jasmine20 on January 21, 2007
  3. Algebra

    1.Simplify x/7x+x^2 A.1/7+x;where x≠-7 B.1/7x;where x≠0 C.1/7+x;where x≠0,-7 D.1/7**** 2.Simplify -12x^4/x^4+8x^5 A.-12/1+8x;where x≠-1/8**** B.-12/1+8x;where x≠-1/8,0 C.-12/9x;where x≠0 D.-12/9 3.Simplify

    asked by GummyBears on May 11, 2016
  4. algebra

    How do you simplify [2/(x+4)]+2 ----------- [3/(x+4)]+1 I know the answer is 2(x+5)/(x+7), but I have little idea how to get there! Please help?! multiply your fraction by (x+4)/(x+4) you end up with [2 + 2(x+4)]/[3 + (x+4)]

    asked by Lydia on May 9, 2007
  1. Algebra 1B

    I really need help with this but I'm not sure if I'm going to put it in the correct form. The problem says to multiply and simplify by factoring. Assume that all expressions under radicals represents nonnegative numbers. Simplify

    asked by LeAnn/Emergency on February 28, 2010
  2. Algebra

    Can you please check my work? You have helped other students I know. Thank you:) Multiply -7(2a2 -4) = -14a2 + 28 Multiply 0.5(a + b -5) = 0.5a + 0.5b - 2.5 Factor bx - by + bz = b(x - y + z) Combine like terms (simplify) 12x + 4

    asked by Sharon (ms. Sue) on November 8, 2011
  3. Algebra (check my answers)

    Please check these answers. Multiply -7(2a2 -4) = -14a2 + 28 Multiply 0.5(a + b -5) = 0.5a + 0.5b - 2.5 Factor bx - by + bz = b(x - y + z) Combine like terms (simplify) 12x + 4 - 11y - 6x - 9 - y = 6x - 12y - 5 Evaluate the

    asked by Sharon on November 8, 2011
  4. algebra,math

    My qustion is for the following the problem reads as follows (x-1)^2 = 7 x-1=+- sqrt 7 x= 1+- sqrt 7 the method they use was factoring in order to simplify the equation to make it easier is this correc? x^2-9x-4=6 x^2-9x-10=0

    asked by jasmine20 on April 2, 2007
  1. Algebra

    Simplify by using factoring:(2a+6b)(6b−2a)−(2a+6b)^2 Thanks for helping!

    asked by Anonymous on April 18, 2018
  2. Math

    Simplify by factoring. radical 90

    asked by Bryan Martin on May 21, 2009
  3. Math

    Simplify by factoring. ^3sqrt 54x^8

    asked by Sam on February 24, 2008
  4. trigonometry

    can i use factoring to simplify this trig identity? the problem is sinx + cotx * cosx i know the answer is cscx and i know how to get it but i want to know if i can do factoring to get it bc i tried to but it wont give me the

    asked by v on December 3, 2012

You can view more similar questions or ask a new question.